Optimizing Electrochemical Performance: A Study of Aqueous Electrolytes with Hemp-Derived Activated Carbon for Supercapacitors - Kanisorn Klangvijit; Khemjiranee Bowornthommatadsana; Mayuree Phonyiem Reilly; Teerayut Uwanno; Visittapong Yordsri; Michiko Obata; Masatsugu Fujishige; Kenji Takeuchi; Winadda Wongwiriyapan (My University, 2025)
This work investigates the synthesis and electrochemical performance of hemp-derived activated carbon (HAC) for supercapacitor electrode applications. HAC was prepared through NaOH chemical activation, and its electrochemical characteristics were evaluated using three different electrolytes: acidic (H2SO4), neutral (Na2SO4), and basic (KOH). The specific surface area of HAC was found to be exceptionally high, measuring 2612 m2/g, surpassing that of commercially available activated carbon (AC). Surface analysis revealed the presence of an oxygen functional group, which provided additional pseudocapacitive active sites. When 1 M H2SO4 was employed as the electrolyte, HAC demonstrated a maximum specific capacitance of 594 F/g (302.4 F/cm3) at a current density of 0.3 A/g. Notably, the HAC electrode exhibited significantly higher energy density and power density, reaching values of 82 Wh/kg (135.7 mWh/cm3) and 188 W/kg (311 mW/cm3), respectively, when compared to commercial AC. These results highlight the potential of HAC as a cost-effective and high-performance electrode material, particularly when paired with H2SO4 as the electrolyte due to their ideal micropore/mesopore ratio for H2SO4 electrolyte access.
Keywords: Supercapacitor Materials and Fabrication